2010
DOI: 10.1093/annonc/mdq066
|View full text |Cite
|
Sign up to set email alerts
|

No protection of the ovarian follicle pool with the use of GnRH-analogues or oral contraceptives in young women treated with escalated BEACOPP for advanced-stage Hodgkin lymphoma. Final results of a phase II trial from the German Hodgkin Study Group

Abstract: We observed no protection of the ovarian reserve with hormonal co-treatment during BEACOPPesc. This result supports efforts of ongoing trials to reduce chemotherapy intensity and toxicity. Alternative strategies for the protection of fertility must be offered to young female HL patients before the start of BEACOPPesc therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 44 publications
2
100
1
9
Order By: Relevance
“…These patients are in the greatest risk of chDOR and also other means of fertility preservation as oocyte/embryo or ovarian tissue cryopreservation should be offered to them prior initiation of chemotherapy, if possible. Our observations are consistent with previous studies that also indicated limited or no protection of the ovarian follicle pool with GnRH-a in young women treated with EB chemotherapy -regimen C in our study [13,17].…”
Section: Discussionsupporting
confidence: 93%
“…These patients are in the greatest risk of chDOR and also other means of fertility preservation as oocyte/embryo or ovarian tissue cryopreservation should be offered to them prior initiation of chemotherapy, if possible. Our observations are consistent with previous studies that also indicated limited or no protection of the ovarian follicle pool with GnRH-a in young women treated with EB chemotherapy -regimen C in our study [13,17].…”
Section: Discussionsupporting
confidence: 93%
“…122 Some studies, including randomized trials, have evaluated the role of menstrual suppression with gonadotropin-releasing hormone (GnRH; also known as LH-releasing hormone [LHRH]) agonists to preserve ovarian function during chemotherapy. [123][124][125][126][127][128][129][130][131] Some meta-analyses have shown that GnRH agonist may be beneficial for fertility preservation. [132][133][134] However, the impact of these meta-analyses are limited by flaws such as only examining women with breast cancer and only including trials that were not adequately powered and did not use blinding and/ or a placebo condition.…”
Section: Options For Femalesmentioning
confidence: 99%
“…In addition, the authors noted that chemotherapy resulted in a similarly decreased ovarian reserve in both groups, as measured by inhibin B and anti-Mullerian hormone (AMH). The same conclusion was reached by another randomized trial in patients with Hodgkin lymphoma [27]. This study was prematurely closed when a 12-month interim analysis showed goserelin-treated patients having the same degree of acute and chronic insufficiency as women treated with oral contraceptives, as reflected by menstrual patterns and AMH and FSH measurements.…”
Section: Ovarian Suppressionmentioning
confidence: 73%